Biological activity of some phenolic compounds extracted from Agrimonia eupatoria against several pathogenic bacteria species (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Mohammed MA, Ali JF, Saeed YS, Yaseen IH, Ahmad BH. 2022. Biological activity of some phenolic compounds extracted from Agrimonia eupatoria against several pathogenic bacteria species. Biodiversitas 23: 4912-4917. Agrimonia eupatoria L. (Rosaceae) has been used for centuries in traditional medicine to overcome infectious diseases. This study was carried out to isolate, characterize, and determine the antibacterial activity of natural compounds obtained from A. eupatoria aerial parts. Three solvents were used in the extraction process. First, hexane was used for defatting plant samples. Then ethyl acetate and ethanol were used to obtain the fraction containing phenolic compounds and their antibacterial activity against several bacteria. The current study identifies several phenolic compounds isolated from A. eupatoria, including gallic acid, salicylic acid, cinnamic acids, and resorcinol, using thin layer chromatography (TLC) and high-performance liquid chromatography (HPLC). In addition, the disc diffusion method was used to determine the antimicrobial activity of several phenolic compounds against four bacterial isolates, i.e., Corynebacterium diphtheria, Bacillus cereus, Salmonella typhymurium, and Enterococcus faecalis. The results indicated that the plant compounds had an antibacterial activity proportional to the concentration. The B. cereus was the most sensitive to the compound isolated from A. eupatoria, followed by C. diphtheria, whereas S. typhimurium exhibited the most insensitive.
Keywords: Agrimonia eupatoria, antimicrobial activity, cinnamic acids, gallic acid, HPLC, resorcinol, salicylic acid